Effect of anesthesy materials on stunning time, water quality, waking time, and blood glucose of carp fish (Cyprinus carpio) - Riki Kurniawan; Roni Nugraha; Nur Alifah Khairi (Jurnal Perikanan Terpadu, 2025)
Fishery commodities in a live condition are preferred and demanded by consumers. The stunning method (anesthesia) is an important solution to reduce fish metabolism during transportation, so that fish are more resistant to stress and mortality can be reduced. One of the methods of stunning that can be done is using natural anesthetic ingredients, namely clove and lemongrass oil. This study aims to determine the natural anesthetic ingredients on fainting time, recovery time, water quality, and blood glucose of carp (Cyprinus carpio). The study used experimental method and the data were analyzed descriptively. Clove oil showed the fastest stupor time compared to lemongrass oil and β-hydroxyethyl phenyl ether with an average initial sedation time of 1 minute 48 seconds and a stupor time of 3 minutes 3 seconds. Meanwhile, the time required to get fit to get fit again is an average of 2 minutes 44 seconds and 7 minutes. Clove oil influenced the fastest behavioral response by giving the effect of fainting at the 5th minute and the slowest total operculum opening of 182. Water quality, namely temperature (29.1℃ to 29.15℃) and ammonia (0 to 0.5 ppm) increased, while DO (5.9 to 4.95 mg/L) and pH (7.33 to 6.67) decreased after being given clove oil. The blood glucose of goldfish was normal after stunning using clove oil at 76 mg/dL. Clove oil has the potential to be a natural anesthetic for goldfish stunning.